The Russian-Ukrainian Earnings Divide - Amelie F. Constant; Martin Kahanec; Klaus F. Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
Ethnic differences are often considered to be powerful sources of diverse economic behavior. In this paper, we investigate whether and how ethnicity affects Ukrainian labor market outcomes. Using micro data from the Ukrainian Longitudinal Monitoring Survey (ULMS) and Oaxaca-Blinder decomposition of earnings, we find a persistent and rising labor market divide between ethnic Russians and Ukrainians throughout Ukraine?s transition era. We establish that language rather than nationality is the key factor behind this ethnic premium favoring Russians. Our findings further document that this premium is larger among males than among females.
Keywords: J70; J15; J82; 330; Ethnicity; earnings differences; discrimination; transitional labor markets; ethnic premium; Arbeitsmarktdiskriminierung; Ethnische Gruppe; Russen; Ukrainer; Systemtransformation; Ukraine